Absentéismes scolaires - Michèle Becquemin; Julie Couronné; Aurélia Mardon (Sociétés et Jeunesses en Difficulté)
This article seeks to describe the different ways in which students can fall short of their mandatory schooling obligations. To that end, it focuses on cases which result in legal reprimand. Is absenteeism more common in certain social settings?  What arguments do pupils and parents present to school authorities to explain absenteeism? Drawing upon observations during 60 interviews and after the study of 250 files involving reported absent pupils, the authors rank the motives identifying six main streams of absenteeism. Nevertheless the wide variety of motives reveals a number of unanticipated social situations. On the whole, instances of absenteeism seem to reveal the weakening of a fraction of the middle class, as well as increased difficulties for the lower classes and notably the banishment of the lowest classes from the school system.  These phenomena go hand-in-hand with the weakening of the educational offer to teenagers who, for the greater part, eventually turn away from the school system and to give up the accomplishment of themselves in this way.